Physiochemical characteristics during potassic alteration of the porphyry copper deposit at Ajo, Arizona - UyTana, Veronica Feliciano (The University of Arizona., 1983)
Potassium metasomatism is a widespread alteration type in porphyry copper deposits and is often spatially associated with hypogene sulfide ore formation. At Ajo, potassic alteration composes the dominant alteration type and is spatially, and to some extent, temporally, associated with chalcopyrite and bornite mineralization. Physiochemical conditions prevailing during potassic alteration thus describe a significant portion of the hydrothermal ore-forming process. Studies of fractures, fluid inclusions in quartz, and structural and compositional characteristics of K-feldspar, all in the potassic alteration zone at Ajo, indicate that: fracturing was strongest during potassic alteration and sulfide deposition, pressure were at approximately 650 bars, temperatures started a a minimum of 580°C, continued through 470°C, log aK+/aH+ changed from 2.6 at 580°C to 3.2 at 470°C, log aNa/aH+ changed from 2.7 at 580°C to 3.8 at 470°C, and the ratio aK+/aNa+ radically decreased from 0.8 to 0.3 in this temperature range.